Peri-postoperative Atrial Fibrillation in Non-cardiothoracic Surgeries: Approach of the Anesthesiologist - Hülya Yılmaz Ak; Kübra Taşkın; Kerem Erkalp (Bagcilar Medical Bulletin, 2022)

(untitled)
In this study, our aim was to summarize the current knowledge on the epidemiology, pathophysiology and management of new-onset perioperative and postoperative atrial fibrillation (POAF) in non-cardiothoracic surgery and to provide a practical approach for anesthesiologists and non-cardiologist clinicians. Various findings such as age, hypertension, diabetes mellitus, cardiac risk factor, premature beats on preoperative electrocardiogram, left anterior fascicular block or left ventricular hypertrophy pose an elevated risk for POAF. The first thing to do in patients with POAF is to determine the origin of the arrhythmia. In most cases, identifying and eliminating the triggering cause will suffice. On the other hand, hemodynamic data should be evaluated. The primary goal of treatment in patients with life-threatening symptoms is to maintain hemodynamic stability. Deterioration of hemodynamic stability and development of shock with AF with high ventricular rate is a condition that requires immediate cardioversion. Rate control therapy increasing dose with continuous cardiac monitoring to a heart rate <110 should be performed on hemodynamically stable patients with POAF. β-blockers and non-dihydropyridine calcium channel blockers (diltiazem and verapamil) are used for rate control in AF. If there is peripheral vascular disease, congestive heart failure, diabetes, hypertension or history of thromboembolic event, attention should be paid and postoperative bleeding risk should be calculated. There is a risk of bleeding in the postoperative period and POAF usually lasts less than 24 hours and improves spontaneously, and the use of heparin at a therapeutic dose is not required. As a general rule, therapeutic doses of anticoagulants are recommended for POAF lasting longer than 48 hours and for frequent recurrent AF attack.